Socioemotional Discourse and Shared Knowledge Construction in Online Collaborative Tasks - Castellanos-Ramírez, Juan Carlos; Niño-Carrasco, Shamaly Alhelí; Parra-Encinas, Karla Lariza (Revista Electrónica Educare, 2020)
The socioemotional discourse of students plays a fundamental role in online collaborative learning. Therefore, they must build a climate of mutual trust that allows them to hold deep, critical, and constructive discussions about the task’s contents, to improve their construction of knowledge. The research was carried out in a Mexican public university where asynchronous collaborative processes developed by three groups of students were analyzed online. The socio-emotional discourse that groups of students use in different phases of the process of shared knowledge construction is explored through the technique of content analysis. The results highlight, on the one hand, seven different types of social-emotional discourse that groups of students frequently use during their collaboration process. On the other hand, it seems that the frequency has an important impact on the construction of knowledge. It is concluded that a dense, frequent, and heterogeneous socio-emotional discourse, in terms of its typology, provides the necessary bases for student groups to develop successful collaborative processes and achieve high levels of shared knowledge construction.